Being in Place: A Multimodal Analysis of the Contribution of the Patient's Companion to “First Time” Oncological Visits - Fatigante, Marilena; Zucchermaglio, Cristina; Alby, Francesca (Frontiers in Psychology, 2021)
Companions to medical visits have been alternatively viewed as members who “support” or “inhibit” and “interfere” with the doctor-patient interaction. One way of looking at the companions' contribution to medical visits is by coding roles or functions of their communicative behavior. Our paper aims at reconsidering these findings and analyzing how the companion participation is a local and sequential accomplishment, changing from time to time in the consultation. The paper relies upon an overall collection of 58 videorecordings of first oncological visits. Visits were conducted in two different hospitals, one of which a University hospital, and by different oncologists, including both senior professionals and (in the second setting) medical students in oncology. Visits were fully transcribed according to the Jeffersonian conventions and authors examined the transcripts and video according to the methodology of Conversation Analysis. The aim of the paper focused on how patient's companions orient and contribute to the accomplishment of the different aims and activities at different stages of the visit as an institutional speech event. The multimodal analysis of turns and actions (such as, gaze shifts, prosodic modulation, bodily arrangements), and the close examination of the sequential and temporal arrangements of companions' and their co-participants' turns revealed that companions finely attune to the multiparty framework of the encounter and the institutional constraints that govern the oncological first visit. Overall, results show two relevant features: that companions act as to preserve the doctor-patient interaction and to maintain the patient as the most responsible and legitimate agent in the interaction; that companions' contributions are relevant to the activities that sequentially unfold at different stages in the consultation (e.g., history taking, problem presentation, treatment recommendation etc.). The study complements earlier findings on the companion's roles, showing how these are highly mobile, multimodal and multiparty accomplishments, and they are tied to the specific contingencies of the visit. The results solicit to consider the value of multimodal analysis in understanding the complexity of multiparty communication in medical setting, and make it usable also in medical education.